Scalable recycling and characterization of end-of-life solid oxide cell ceramic component materials - Gudaysew Tsegaye Yenesew; Clément Nicollet; Eric Quarez; Annie Le Gal La Salle; Olivier Joubert (Next Sustainability)
By recycling solid oxide cells (SOCs) end-life materials, the environmental impact can be reduced, and the materials' closed-loop life cycle can help preserve natural resources and create a sustainable and circular system. This study presents a technique for recovering NiO, LaxSr1-xCoO3 (LSC) and Zr1-xYxO2-x/2 (YSZ) components from SOC end-of-life products. First, the entire cell components, including the electrolyte, fuel and air electrodes were crushed, ball-milled, and leached with nitric acid. Following the maximum dissolution of cations, centrifugation was used to remove the non-leached YSZ as a sediment. The leached solution, which is rich in nickel, cobalt, strontium, and lanthanum ions was treated with dimethylglyoxime (C4H8N2O2 DMG) and Ni is preferentially precipitated as C8H14N4NiO4. LSC is then recovered from thermal treatment of solution leftover from C8H14N4NiO4 centrifugation and filtration. About 90 wt% of the ceramic components were successfully recovered. The compositions of recovered materials show a commercial-grade purity i.e about 99 at% for NiO, 96 at% for LSC and 97 at% for YSZ.